2017
DOI: 10.1051/0004-6361/201628967
|View full text |Cite
|
Sign up to set email alerts
|

Determination of robust metallicities for metal-rich red giant branch stars

Abstract: Context. The study of the Milky Way relies on our ability to interpret the light from stars correctly. With the advent of the astrometric ESA mission Gaia we will enter a new era where the study of the Milky Way can be undertaken on much larger scales than currently possible. In particular we will be able to obtain full 3D space motions of red giant stars at large distances. This calls for a reinvestigation of how reliably we can determine, e.g., iron abundances in such stars and how well they reproduce those … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 59 publications
1
1
0
Order By: Relevance
“…Zoccali et al (2004) derived a value of -0.10 dex in three stars and Harris (1996Harris ( , 2010 quotes a metallicity of -0.11 dex for NGC 6528. Liu et al (2017) found a metallicity of 0.04 dex with a scatter of 0.07 dex, their S/N is similar to ours. Moreover, we have three stars in common (see table 2), with good agreement for star #3 and #6.…”
Section: Ironsupporting
confidence: 89%
See 1 more Smart Citation
“…Zoccali et al (2004) derived a value of -0.10 dex in three stars and Harris (1996Harris ( , 2010 quotes a metallicity of -0.11 dex for NGC 6528. Liu et al (2017) found a metallicity of 0.04 dex with a scatter of 0.07 dex, their S/N is similar to ours. Moreover, we have three stars in common (see table 2), with good agreement for star #3 and #6.…”
Section: Ironsupporting
confidence: 89%
“…Table 1 lists the stellar parameters of our sample: ID, the J2000 coordinates (RA and Dec), J, H, K s magnitudes from VVV PSF photometry (de-reddened), calibrated on the system of 2MASS (Mauro et al 2014;Cohen et al 2017), heliocentric radial velocity, Teff, log(g), metallicity and micro-turbulent velocity (v t ). Moreover, Table 2 shows the metallicity values from Saviane et al (2012), Mauro et al (2014) and Liu et al (2017).…”
Section: Observations and Data Reductionmentioning
confidence: 99%